2004
DOI: 10.1002/uog.941
|View full text |Cite
|
Sign up to set email alerts
|

Width of the fetal lateral ventricular atrium between 10 and 12 mm: a simple variation of the norm?

Abstract: Objectives The prognosis of borderline forms of anomalies that can be detected by ultrasound is one of the most challenging issues in prenatal diagnosis. The aim of this study was to determine the prognosis for fetuses presenting with isolated mild ventriculomegaly (MVM). Methods Fetuses in which the width of the lateral ventricular atria was 10–12 mm and which had no other detectable chromosomal or morphological anomalies were followed by monthly ultrasound examinations until delivery. For the cases identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 18 publications
0
96
1
2
Order By: Relevance
“…Therefore, it is of interest to know the outcome of fetuses with isolated VM. The incidence of perinatal and neonatal death is higher in cases of severe (>15 mm) and moderate (12-15 mm) VM about 25 and 10%, respectively, while it is comparable to that of the general population in cases of mild VM (10-12 mm) (Vergani et al, 1998;Pilu et al, 1999;Graham et al, 2001;Signorelli et al, 2004;Gaglioti et al, 2005). However, the number of cases is too small in order to draw final conclusions.…”
Section: Outcome Of Isolated Vmmentioning
confidence: 81%
See 1 more Smart Citation
“…Therefore, it is of interest to know the outcome of fetuses with isolated VM. The incidence of perinatal and neonatal death is higher in cases of severe (>15 mm) and moderate (12-15 mm) VM about 25 and 10%, respectively, while it is comparable to that of the general population in cases of mild VM (10-12 mm) (Vergani et al, 1998;Pilu et al, 1999;Graham et al, 2001;Signorelli et al, 2004;Gaglioti et al, 2005). However, the number of cases is too small in order to draw final conclusions.…”
Section: Outcome Of Isolated Vmmentioning
confidence: 81%
“…VM is severe when the measurement of the ventricular width is >15 mm, or ≥15 mm according to different authors (Den Hollander et al, 1998;Graham et al, 2001;Gaglioti et al, 2005;Breeze et al, 2007); it is defined mild or borderline when the measurement is less (Wax et al, 2003;Wyldes and Watkinson, 2004). Recent data would suggest to further divide borderline VM into mild (10-12 mm) and moderate (>12-15 mm) (Signorelli et al, 2004;Gaglioti et al, 2005;Salomon et al, 2006;Falip et al, 2007).…”
Section: Prenatal Definitionsmentioning
confidence: 99%
“…Fetuses with isolated mild ventriculomegaly have the most favourable outcomes (Signorelli et al, 2004;Breeze et al, 2005) with a 7-10% risk of learning difficulties (Vergani et al, 1998;Pilu et al, 1999;Gaglioti et al, 2005). There is, however, a lack of outcome data on 'apparently' isolated SVM that can be used to counsel on survival rates and neurodevelopmental outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Mild VM may also be the first sign of brain anomalies recognizable only in the third trimester or even after delivery, such as cortical malformations. The mean percentage of anomalies not recognized at the time of the first diagnosis of mild VM is 12.8% [3,11,13,15,18,20,27]. A more recent review of nine studies reporting data on postnatal imaging, showed a prevalence of previously undiagnosed findings of 7.4% [21].…”
Section: Ruling Out For Associated Anomaliesmentioning
confidence: 99%
“…Measurements between 10 and 15 mm constitute mild VM, also defined as borderline ( Figure 1); values above 15 mm constitute severe VM. Some authors [27] use the term "milder VM" and "moderate VM" to indicate measurements of 10-12 and 12.1-15 mm, respectively. Other authors [4] restrict the term "mild VM" to measurements between 10 and 12 mm.…”
mentioning
confidence: 99%